Detection of human papillomavirus by hybrid capture and real time PCR methods in patients with chronic cervicitis and cervical intraepithelial neoplasia - Khandker, Elisha (IMC Journal of Medical Science, 2017)
Background and objectives: Cervical cancer due to Human papillomavirus (HPV) is one of the leading causes of morbidity and mortality in women. Testing of HPV can identify women who are at risk of cervical cancer. Nowadays, molecular methods like real time polymerase chain reaction (PCR) and hybrid capture technique are applied for detecting HPV in cervical specimens. The objective of the present study was to determine the rate of HPV infection in women with chronic cervicitis and cervical intraepithelial neoplasia (CIN) by a commercial real time polymerase chain reaction test kit and by a hybrid capture HPV DNA test. Methods: Women aged between 20 to 55 years with chronic cervicitis and CIN were enrolled in the study after obtaining informed consent. Cervical specimen was collected by using cervical brush and stored in transport medium until used. HPV was detected by High Risk Screen Real-TM Quant 2x (Sacace, Biotechnologies SrI, Italy) real time PCR kit (HR RT-PCR) and by Hybrid Capture-2 High-Risk HPV DNA (Hc-2; Digene Corporation, USA) test. Results: Total 72 women with chronic cervicitis and CIN of different grades were included in the study. Out of this, HPV infection detected by HR RT-PCR was 31 (43%) and by Hc-2 was 14 (19.4%). Both the tests were able to detect HPV infection in all the CIN 3 cases and in most of the CIN 2 cases. However, HR RT-PCR detected higher number of HPV in chronic cervicitis and CIN1 cases. Conclusion: The study has shown that HR RT-PCR and Hc-2 tests are equally effective in detecting HPV infection in patients with CIN 2 and CIN 3 lesions. However, HR RT-PCR is more sensitive test for detecting HPV in chronic cervicitis and early CIN lesions and, therefore can be used in epidemiological study to detect presence of HPV in general population. IMC J Med Sci 2016; 10(2): 45-48